2011
DOI: 10.1371/journal.pone.0019228
|View full text |Cite
|
Sign up to set email alerts
|

Serum Fetuin-A Associates with Type 2 Diabetes and Insulin Resistance in Chinese Adults

Abstract: BackgroundPrevious studies have demonstrated that fetuin-A is related to insulin resistance among subjects with normal glucose tolerance but not patients with type 2 diabetes. There are limited data available concerning fetuin-A and insulin resistance in Chinese. We aimed to study the association of feuin-A with insulin resistance among participants with or without type 2 diabetes in a large sample size of adults aged 40 and older.Methodology and Principal FindingsA community-based cross-sectional study was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
57
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 33 publications
14
57
1
5
Order By: Relevance
“…Our results are consistent with those described in previous studies (20,21). Moreover, serum fetuin-A is related to prediabetes, diabetes type 2, and IR in Chinese population aged ≥40 years (22). …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are consistent with those described in previous studies (20,21). Moreover, serum fetuin-A is related to prediabetes, diabetes type 2, and IR in Chinese population aged ≥40 years (22). …”
Section: Discussionsupporting
confidence: 93%
“…Our study demonstrated that serum fetuin-A was related to IR, and HOMA2IR index and fasting insulin serum levels were increased; this result is consistent with previous results (4,(22)(23)(24). Therefore, fetuin-A may be used as a new factor implicated in T2DM pathology and physiology; IR also plays an important role in the T2DM mechanism (25).…”
Section: Original Articleesupporting
confidence: 91%
See 2 more Smart Citations
“…It is more abundant in fetal than adult circulation (4) and synthesized in the liver secreted into serum processed from a single chain precursor to the mature circulating twochain form by proteolytic processing in the Golgi apparatus to form a light and a heavy chain consisting of 27 and 321 amino acids, respectively. The mature form of fetuin-A has three domains so this complex structure of fetuin-A suggests multiple biological functions.…”
Section: Introduction:-mentioning
confidence: 99%